1037 Determination of Prealbumin, Selenium, Zinc and Iron Concentration in Serum for Monitoring the Nutrition Status of Phenylketonuric and Hyperphenylalaninemic Patients. (October 2012) - Prochazkova, D; Kolbova, L; Jarkovsky, J; Vinohradska, H; Konecna, P; Dolezel, Z
Abstract : Background and Aims: Phenylketonuria is an inherited disorder of metabolism of the amino acid phenylalanine caused by a deficit of the enzyme phenylalaninhydroxylase. It is treated with a low-protein diet containing a low content of phenylalanine to prevent mental affection of the patient. The objective of the present study was to assess the compliance of our phenylketonuric (PKU) and hyperphenylalaninemic (HPA) patients; to determine the concentration of serum pre-albumin and trace elements to discover the potential correlation between the amount of proteins in food and their metabolic control. Methods: The prospective study contained altogether 174 patients, of which 113 were children, 60 with PKU and 53 with HPA and 61 were adults, 51 with PKU and 10 with HPA. Results: We did not prove a statistically significant difference in the levels of serum pre-albumin, zinc and iron among the respective groups. We proved statistically significant difference in the level of serum selenium among PKU and HPA patients in adulthood (p=0.006, Mann-Whitney U test). Conclusion: The therapeutic restrictive diet for PKU and HPA makes the patient liable to the risk of nutritional deficit.